Long COVID-19 “A Metabolic Sequela,” the New-Onset Diabetes among Cohorts Admitted at Tertiary Care Hospital, Hyderabad - Sudha Bala; Surendra B Darivemula; Shrikanth Muralidharan; Rajiv K Bandaru; Sushma N Katkuri; Anesha Singireddy (Journal of Diabetology)
Abstract Introduction: Long COVID is now being encountered by many individuals during this pandemic. It is best diagnosed by a history consistent with acute COVID-19 followed by a prolonged recovery. Aim: This study was undertaken to detect new-onset diabetes mellitus among COVID cohorts and their associated factors. Materials and Methods: A total of 152 COVID-19 patients admitted at ESIC medical college and hospital without a known history of diabetes mellitus were included in the study. Data were collected about sociodemographic variables, their symptoms at presentation, lifestyle determinants, and measurement of blood sugar by HbA1C for a period of 6 months follow-up with three readings (baseline, third month, and sixth month) using a predesigned and pre-tested questionnaire schedule. Results: Mean HbA1c was found to be 7.28 ± 2.09 at the third reading with new-onset diabetes mellitus development among 38 (25%). There was a positive correlation between age and mean HbA1c measurement on follow-up. Significant risk factors were the presence of comorbidities OR = 15.23 (4.42–22.46), sedentary lifestyle 6.14 (1.39–9.11), tobacco usage 6.80 (2.63–14.55), symptomatic COVID-19 presentation 2.43 (1.11–5.41), alcohol usage 2.11 (0.99–4.49) and extra physical activity 1.72 (0.66–2.32). Conclusions: There was a quarter of patients with new-onset diabetes mellitus in the present study. This will help us to identify the risk factors of this sequela at the earliest for initiating preventive strategies at the primary care level.